CONDENSATION REACTIONS OF 1,3-DIPHENYL-2-PROPEN-1-0NES WITH NUCLEOPHILIC REAGENTS - REHMAN, A. U.; QURESHI, M.A. (Biological Sciences - PJSIR, 2022)
The reactivity of substituted I,3-diphenyl-2-propen-l- ones has been investigated under acidic and basic conditions with amino-compounds resulting to heterocyclic derivatives. Other reactions with ethyl acetoacetate and acetylacetone have afforded substituted 3,S-disphenylcyclohexenones.